TRANSDISCIPLINARY MODEL OF A CONTEMPORARY EFFECTIVE MANAGER - N. Khmelkova (Управленческие науки, 2015)
Russian economy is experiencing a severe shortage of Managerial Human Resources being increased against the background of modernization-based vector. The lack of competent supervisors leads to scarcity of reference models necessary for the formation of new-generation managers.There is no consensus regarding the training of modern effective manager, some specialists show leveling the valuables of fundamental education in the sphere of management advocating for its substitution by short-term business courses and practical experience.The author of the article states that in current conditions managers need new essential competences enabling them to renew the knowledge very fast and see the wide market context. For this purpose it’s necessary to form a new kind of manager-the manager-intellectual possessing transdisciplinary world view. Dangerously hollow attitude towards the management education of some experts is connected with the fact that the position of management and its scientific constituents in the system of narrowly disciplined knowledge remain undefined.With the appearance of transdisciplinary paradigm gaining the authority and popularity as a methodological basis for convergence of sciences, technologies and other knowledge spheres in order to study the global problems and forming the wide consensus in scientific and educational community the status of managerial disciplines must undergo the drastic changes. The author suggests that in order to manage people, assets, processes effectively the modern managers must cognize the subject of management across the spectrum of all its forms, understand and adopt its complicated nature as well as master to work in this not easy reality.